Analisis Yuridis Pembuatan Perjanjian Baku Dalam Perjanjian Kredit Perbankan Berdasarkan Seojk No. 13/SEOJK.07/2014 (Studi Kasus Putusan No. 888/Pdt.G/2023/PN Jkt.Sel) - Timothy Putra Natama Parulian Siregar; Mahmud Aqil; Muhammad Fairuz; Natanael Robona Asimi Siagian; Dwi Desi Yayi Tarina (Media Hukum Indonesia (MHI), 2026)
Banking credit agreements are generally drafted in the form of standard contracts (perjanjian baku) unilaterally determined by banks as financial service providers. This practice creates an imbalance in bargaining power between creditors and debtors that potentially prejudices consumer interests. In Decision No. 888/Pdt.G/2023/PN Jkt.Sel, the Plaintiff argued the existence of standard clauses that violated consumer protection provisions and sought annulment of the credit agreement along with all its accessory agreements. This article analyzes the conformity of standard contract drafting in banking credit with SEOJK No. 13/SEOJK.07/2014, specifically regarding the principle of balance, prohibition on certain clauses, transparency aspects, and the format of standard agreements. This research employs a normative juridical method with statutory, case, and conceptual approaches. The analysis reveals that the credit agreement in question constitutes a standard contract within the meaning of SEOJK No. 13/SEOJK.07/2014. Clauses granting the bank unilateral authority to establish new provisions potentially violate the principle of balance and standard clause prohibitions. However, alleged clause violations do not automatically nullify the entire agreement but only affect the enforceability of the specific clause concerned. This decision also affirms the importance of jurisdictional competence in banking disputes, demonstrating that dispute resolution is determined not only by clause substance but also by procedural aspects and the agreed forum for dispute resolution.